Representation and Space: The Discursive Construction of Ortabahçe at the Faculty of Language, History and Geography - Hasan İçen; Ahmet Uysal (İstanbul Üniversitesi Sosyoloji Dergisi)
The shift of interest in the time-space duality in favor of space is a phenomenon that can be seen within the relations extending between the modern and post-modern periods. As a result of this process, space and place have become central concepts in social and individual life, and thus various studies have focused on these concepts, with some studies addressing an understanding of how space transforms into place and what place really means. In this regard, representation as a functional concept is seen to occur in the foreground. Representation is related to how an individual creates, transfers, and reproduces meaning. In short, representation is the reproduction of reality. Places in daily and social life have meanings that are processed and reproduced by subject, and these representations experience a constant state of motion, especially with the help of language. In this respect, the spaces and places of daily and social life can be studied from the perspective of the concepts of language and representation. Ortabahçe is the courtyard in the middle of the Faculty of Languages and History-Geography. It was established in Ankara in 1935 and emerged in 1974 as an area where one can observe the social, political, and economic adventure of the country. Ortabahçe’s reflections can be observed as an actual place in social and individual life. This study examines Ortabahçe through the concept of representation and attempts to understand the process of transforming space into place. The study uses mixed methods and has revealed how the meanings, representations, and discourses of space have diversified.